Ressentiments towards digital humanities and how to deal with it - Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2018)
Junior researchers who analyse their sources with digital approaches can profit from productive environments where the advantages and potentials of these techniques are well known and established. …